Comparison of the purified terpenoid fractions of thuidium tamariscellum (c.muell.) Bosch. & sande-lac and brachythecium buchananii (hook.) A. Jaeger by Gc-ms/ms analysis (Funded Work) - GREESHMA GM; MURUGAN K (International Journal of Pharma and Bio Sciences, 2018)
Terpenes are isoprenoid polymers and are arranged in a regular head to tail pattern. The side chains of Vitamin A, E, K, squaleneare constituents of terpenes. They usually emit fragrances as insect repellants, aid in pollination, perfume synthesis, cosmetics and also divesified medicinal values. Similarly, they possess toxic impacts like seizures, CNS depression, nausea and vomiting. The present study was aimed to analyze the terpenoid composition in the column eluted fractions of the two moss species Thuidium tamariscellum and Brachythecium buchananii through GC-MS/MS analysis. The fraction eluted using solvent combinations such as 100% PE, 95:5(Petroleum ether: Ethyl acetate) and 80:20(PE: EA) of Thuidium tamariscellum and 100% PE, 95:5(PE:EA), 90:10(PE:EA) of Brachythecium buchananii revealed the presence of terpenoidsThe 100% PE eluted fraction of T. tamariscellum indicated the presence of 15 compounds α-cubebene, caryophyllene (sesquiterpenoids)followed by 1-tetradecene, dodecanal, tetradecane, heptadecane, pentadecane, hexadecane, eicosane, octadecane, nonadecane, heneicosane, docosane, pentacosane and hexacosane. The 95:5(PE:EA) purified fraction of T. tamariscellum revealed the presence of 9 peaks of terpenoids and 80:20(PE:EA)purified fraction of T. tamariscellum showed the presence of 14 compounds. The 100% PE eluted fraction of Brachythecium buchananii showed 5 compounds, the 95:5 (PE:EA)purified fraction of B. buchananii showed the presence of 7 compounds and the 90:10 (PE:EA)purified fraction of B. buchananii revealed the presence of 5 compounds. The compounds identified were medicinally proven for the treatment of various human diseases like inflammations, cancer etc. Further studies are warranted to identify the lead compound and its biological potentialities.